Anti-inflammatory withajardins from the leaves of Athenaea velutina. (November 2022) - Dantas Rocha, Késya Amanda; de Freitas Paulo, Tércio; Ayala, Alejandro Pedro; da Silva Sampaio, Valéria; Gomes Nunes, Paulo Iury; Santos, Flávia Almeida; Canuto, Kirley Marques; Silveira, Edilberto Rocha; Loiola Pessoa, Otília Deusdenia
Abstract: Withajardins, uncommon modified withanolide-type steroids, have been isolated exclusively from plants of the Solanaceae family so far. Two undescribed withajardins and the known tuboanosigenin were isolated from the hexane/EtOAc 1:1 extract from Athenaea velutina leaves. Their structures were established by an extensive analysis of 1D and 2D-NMR and HRMS data. The absolute configuration was determined by X-ray diffraction (withajardin L and tuboanosigenin) and circular dichroism (CD) analyses (withajardin M). The anti-inflammatory activity of compounds was evaluated through the inhibition of the lipopolysaccharide (LPS)-induced nitric oxide (NO), TNF- α, and IL-6 release in RAW264.7 cells. The cell viability effects to RAW 264.7 cells showed IC50 values of 74.4–354.4 μM. The compounds attenuated LPS-induced release of NO and decreased pro-inflammatory cytokines TNF- α and IL-6 in RAW264.7 cells. Graphical abstract: Image 1 Highlights: Three withajardins were isolated from the leaves of Athenaea velutina. Their absolute configuration was determined by X-ray diffraction and circular dichroism. Compounds reduced TNF-α and IL-6 production in LPS-stimulated RAW264.7 cells.